(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Jaundice, characterized by yellow discoloration of the skin, mucous membranes, and sclera due to elevated bilirubin levels in the blood, is a common clinical symptom that can arise from various underlying conditions. The identification of the specific type of jaundice—pre-hepatic (hemolytic), hepatic (hepatocellular), or post-hepatic (obstructive)—is critical for timely and appropriate treatment. Misdiagnosis or delayed diagnosis can lead to significant morbidity, especially in conditions such as cholestasis, fulminant hepatitis, or malignancies. This article explores the clinical types of jaundice, their etiologies, presentations, diagnostic algorithms, and emphasizes strategies to prevent common diagnostic errors through a detailed review of clinical cases, imaging, and laboratory analysis.